Microstructure and Wear Behavior of CoCrFeMnNbNi High-Entropy Alloy Coating by TIG Cladding - Wen-yi Huo; Hai-fang Shi; Xin Ren; Jing-yuan Zhang (Advances in Materials Science and Engineering)
Alloy cladding coatings are widely prepared on the surface of tools and machines. High-entropy alloys are potential replacements of nickel-, iron-, and cobalt-base alloys in machining due to their excellent strength and toughness. In this work, CoCrFeMnNbNi HEA coating was produced on AISI 304 steel by tungsten inert gas cladding. The microstructure and wear behavior of the cladding coating were studied by X-ray diffraction, scanning electron microscopy, energy dispersive spectrometer, microhardness tester, pin-on-ring wear tester, and 3D confocal laser scanning microscope. The microstructure showed up as a nanoscale lamellar structure matrix which is a face-centered-cubic solid solution and niobium-rich Laves phase. The microhardness of the cladding coating is greater than the structure. The cladding coating has excellent wear resistance under the condition of dry sliding wear, and the microploughing in the worn cladding coating is shallower and finer than the worn structure, which is related to composition changes caused by forming the nanoscale lamellar structure of Laves phase.